MOSAIC, an example of comprehensive and integrated social and health care: care and practices oriented towards personal recovery - Cano-Prieto, Ivan; Prat-Vigué, Gemma; Vilanova-Masana, Rut; Guillaume-Cornet, Aida; Giralt Palou, Rosa; Lana-Francos, Gemma; Simó-Algado, Salvador (Frontiers in Health Services, 2023)
Background: The Mosaic project is a socio-health integration model that promotes the personal recovery of people with severe mental illness in a territory of Central Catalonia. The recovery approach in mental health care promotes meaningful activities and social inclusion for people with mental health disorders. The aim of this study is to examine the relationship between the level of meaningful activities and other factors associated with the mental health recovery model. (2) Methods: A cross-sectional design was used. Participants(n=5) signed an informed consent and completed the following standardized instruments: Engagement in Meaningful Activities Survey; The Connor-Davidson Resilience Scale; Hert Hope Scale; and Recovery Assessment Scale. (3) Results: A Pearson correlation test was performed between the level of meaningful activities and life satisfaction, resilience, hope, and recovery. These data indicate that the amount of meaningful activities are strongly associated with variables related to the personal recovery process from mental health problems. (4) Conclusions: The MOSAIC integration process confirms the need to accompany recovery processes through significant occupations in a reduced sample. Future research needs to quantify the impact of the intervention on the reported outcomes. The project lays the foundations for an ECA, which has to incorporate the criteria of territorial equity.